2023
DOI: 10.1111/apv.12391
|View full text |Cite
|
Sign up to set email alerts
|

How does the ‘Belt and Road Initiative’ change urbanisation patterns in Southeast Asia?

Adèle Esposito Andujar,
Gabriel Fauveaud,
Marie Gibert‐Flutre
et al.

Abstract: This paper examines how Chinese transnational investments, as (re)framed in the Belt and Road Initiative (BRI), contribute to changes in urbanisation processes in Southeast Asia. On the ground, the BRI becomes contextualised and intersects with local and national development trajectories. The growing presence of Chinese actors in the region intensifies urban dynamics, especially in secondary cities and emerging urban sites, where the BRI is used as a lever for local internationalisation strategies. The heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous studies that have sought to quantify changes in land-use have identified several anthropogenic drivers, including socio-economic (e.g., GDP and population), proximity to economic centers or transportation infrastructure, and land-use policies (Naikoo et al, 2022), with FDI increasingly becoming a major determinant in shaping landscape dynamics (Piabuo et al, 2023). Specifically within the BRI, scholars contend that further research and critical analysis are required to enhance our understanding of how the BRI has instigated diverse patterns of urbanization across the different geographical landscapes of recipient countries (Andujar et al, 2024).…”
Section: Patterns Of Fdi-induced Land-use Changementioning
confidence: 99%
“…Previous studies that have sought to quantify changes in land-use have identified several anthropogenic drivers, including socio-economic (e.g., GDP and population), proximity to economic centers or transportation infrastructure, and land-use policies (Naikoo et al, 2022), with FDI increasingly becoming a major determinant in shaping landscape dynamics (Piabuo et al, 2023). Specifically within the BRI, scholars contend that further research and critical analysis are required to enhance our understanding of how the BRI has instigated diverse patterns of urbanization across the different geographical landscapes of recipient countries (Andujar et al, 2024).…”
Section: Patterns Of Fdi-induced Land-use Changementioning
confidence: 99%